Evaluation of the Implementation of Vocational Gas and Arc Welding Subjects in Malaysian Secondary Schools - Rosman, Nurul Azlin; Rozali, Mohd Zulfadli (Online Journal for TVET Practitioners, 2023)
Mata Pelajaran Vokasional Kimpalan Arka dan Gas (MPV-KAG) is an initiative of the Ministry of Education (Malaysia) to provide opportunities for students in academic secondary schools who have not succeeded in getting a place in Sekolah Menengah Teknik (SMT) or Sekolah Menengah Vokasional (SMV). Therefore, this study was conducted to evaluate the readiness for the implementation of vocational subjects (gas and arc welding) in daily secondary schools in Malaysia. A total of 106 students who took the MPV-KAG course at Sekolah Menengah Kebangsaan Malim, Sekolah Menengah Kebangsaan Ledang, Sekolah Menengah Kebangsaan Ungku Husin, and Sekolah Menengah Kebangsaan Ungku Aziz were involved in this study. The questionnaires for this study were distributed to students who took the MPV-KAG course at the four daily secondary schools. This study uses a descriptive analysis method (mean and standard deviation). The reliability value for the study instrument is ? = 0.86. Overall, the results of the study showed that the level of willingness of students to follow MPV-KAG courses, the level of opportunities given by the teacher to the students in doing activities according to their own abilities during the teaching and learning process, and the availability of sufficient, functional, and appropriate workshop equipment facilities throughout the MPV practical class were at a high level, with a mean value of (M = 4.11, M = 4.06, M = 4.29). In conclusion, this study found that the implementation of MPV-KAG in daily secondary schools in Malaysia is in good condition.